Post-marketing safety concerns with Tislelizumab: a disproportionality analysis of the FDA adverse event reporting system - Li, Chen; Ding, Yi; Cai, Shanshan; Liu, Bai Cheng; Wang, Xiufeng (Frontiers in Immunology, 2025)
BackgroundTislelizumab is an anti-programmed cell death protein 1(anti-PD-1) monoclonal antibody, which was approved by the Food and Drug Administration(FDA) on March 14, 2024. However, clinical studies are often limited by small sample sizes, and thus a more comprehensive evaluation of the safety of Tislelizumab, particularly its immune-related adverse reactions, is urgently needed.MethodDisproportionality analysis was used in this study to assess the safety of Tislelizumab in clinical practice by analyzing all adverse event reports from the FDA Adverse Event Reporting System database, starting from the first quarter of 2024, where Tislelizumab was identified as the primary suspected drug. Two disproportionality analysis methods, reporting odds ratio (ROR) and Bayesian confidence propagation neural network (BCPNN), were utilized to investigate the adverse reactions related to Tislelizumab. Additionally, the Weibull distribution was employed to examine the time-dependent changes in the incidence of adverse events.ResultsConsistent with the drug label, this study identified significant positive signals for adverse reactions, including myelosuppression, hepatic dysfunction, pruritus, rash, and exfoliative dermatitis. Notably, this study also identified several adverse reactions not documented in the drug label, including palmar-plantar erythrodysaesthesia syndrome, immune-mediated cystitis, and renal cysts. Adverse reactions associated with Tislelizumab generally manifested within the first month of treatment. In terms of immune-related adverse reactions, Tislelizumab demonstrated lower signal values compared to other immune checkpoint inhibitors.ConclusionThis study comprehensively reviews the safety profile of Tislelizumab, thereby providing clinicians with crucial safety information for prescribing this drug. Due to its relatively low risk of immune-related adverse events (irAEs), Tislelizumab may serve as a promising candidate for combination therapy with other immune checkpoint inhibitors (ICIs). Novel combination strategies involving Tislelizumab and other ICIs are anticipated to provide new therapeutic opportunities for patients experiencing irAEs.